(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
In this research, we are studying the possibility of contribution in solving the Vehicle Routing Problem with Time Windows(VRPTW),that is one of the optimization problems of the NP-hard type. Moreover, Hybrid algorithm (HA) provided that integrates between Tabu Search Algorithm and Guided Local Search algorithm And existence 2- Opt Local Search, based on the savings algorithm in terms of continued of a particular objective to provide a lot of savings. As we will compare the presented approach with standard tests to demonstrate the efficiency, and their impact on the quality of the solution in terms of speed of convergence and the ability to find better solutions.